Evaluation of anesthetic approaches to surgical patients during early COVİD-19 pandemic - Karaca, Ümran; Ata, Filiz; Yılmaz, Canan; Balkaya, Ayşe Neslihan; Onur, Tuğba (The European Research Journal, 2022)
Objectives: We aimed to evaluate the anesthetic approaches of patients who underwent surgery in our hospital during the early COVID-19 pandemic period.Methods: All patients admitted to general surgery (GS), orthopedics, neurosurgery (NS), urology, cardiovascular surgery (CVS), thoracic surgery, ear nose throat, and plastic and reconstructive surgery at the operating rooms in our hospital in early pandemic periods were scanned retrospectively. Demographical data, surgical indications, urgency, anesthetic methods, and complications are evaluated. Anesthetic methods used in the operations were examined as general anesthesia, regional anesthesia, and sedoanalgesia. In addition, patients’ hospital stay period, intensive care unit admission rate, 30 days mortality, and COVID-19 positivity after surgery were examined.Results: Two hundred and ninety patients were admitted for operation in our hospital during a pandemic. CVS, Orthopedics, and GS were departments that admitted the most number of patients with ratios of 27.2%, 26.2%, and 25.2% respectively. The patients who underwent emergency surgery were seen in the CVS with 79 patients and the orthopedics with 73 patients. In anesthesia management, the application rate of general anesthesia was 44.1%, regional anesthesia 33.1%, and sedoanalgesia 22.8%. Totally 61 patients were admitted to ICU. According to surgical branches, 30-day mortality rates were determined as 8.3% in NS, 6.6% in GS, 3.8% in CVS, and 2.7% in orthopedics respectively. Four patients were postoperative COVID-19 positive in total.Conclusions: Anesthetic approaches in surgical patients may affect the length of hospital stay, referral to the intensive care unit, and mortality in the early period of the COVID-19 pandemic.